Characterization of transverse mixing in a screw mixer by image analysis. Issue 2 (25th January 2016) - Huo, Chaofei; Feng, Ping; Fan, Chuigang; Lin, Weigang; Song, Wenli
ABSTRACT: Transverse mixing of particles in a screw mixer is investigated by a digitized image analysis method coupled with a solidification technique. The effects of screw rotation speed, filling level, and particle size on the transverse mixing index and mixing rate constant are investigated experimentally. The results show that a decrease in screw rotation speed and filling level results in an increase in the mixing rate. Faster mixing is observed with large particles, and the mixing rate constant of coarse particles is 1.5–2 times higher than that of fine particles. The particle size difference of materials puts the particles at a risk of segregation.